Mechanical system analysis vibration approach / Jafri Ahem and Jamil Mohd Shah - Ahem, Jafri; Mohd Shah, Jamil (1986)
Mechanical system analysis has long been an important part of the mathematical, physical engineering disciplines. A system in the engineering sense is an entity which can be modeled as a transformation from an input to an output.